Efeito de fertilizantes organominerais no controle de Meloidogyne javanica e na promoção de crescimento em mudas de café (Coffea arabica) - Gonçalves, Maria Júlia Gouvêa (Universidade Federal de São Carlos, 2025)
Root-knot nematodes of the genus Meloidogyne, particularly M. javanica, are among the main phytopathogens affecting coffee seedlings (Coffea arabica L.), compromising early plant development and crop productivity. Given the limitations of synthetic nematicides and the need for more sustainable practices, this study aimed to evaluate the effect of different formulations of organomineral fertilizers and bio-inputs on the control of M. javanica and on the growth promotion of coffee seedlings. The experiment was conducted in a greenhouse at UFSCar – Araras campus, in a completely randomized design with seven treatments and seven replications. The treatments consisted of organomineral fertilizer (FOM) applied alone or combined with castor cake or castor oil, fungal and bacterial bionematicides, Profix, and an inoculated control. The evaluated variables were plant height, biomass (fresh and dry shoot weight, root weight), relative chlorophyll content (FALKER), and nematode population in soil and roots. Statistical analyses were performed using the Sisvar software, through ANOVA and the Scott-Knott test at a 5% significance level. Although the treatments did not promote statistically significant reductions in nematode populations, numerical decreases were observed in some cases, particularly with FOM + castor cake and the bacterial bionematicide. The variables related to plant growth showed better results in treatments with FOM alone, FOM + castor cake, and Profix, demonstrating the potential of these inputs to promote growth even under biotic stress. The results suggest that organomineral fertilizers and plant-based residues are promising alternatives for the sustainable management of coffee seedlings and can be integrated into root-knot nematode management programs.
Effect of organomineral fertilizers on the control of Meloidogyne javanica and on growth promotion in coffee seedlings (Coffea arabica).
Keywords: Fitonematoides; Bioinsumos; Crescimento vegetal; Cafeeiro; Phytonematodes; Bioinput; Plant growth; Coffee tree; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA